Tak Mau Menyerah, Ibu-Ibu Warga Desa Jatiendah Belajar Editing Video dengan Capcut - Ratnadewi Ratnadewi; Aikho Pasodung; Heri Andrianto; Pin Panji Yapinus; Meythi Meythi (Jurnal Atma Inovasia, 2025)
Residents of RT 5, RW 3, Jatiendah Village, mostly earn as construction workers, open stalls, and sell food. The women in Jatiendah Village, who are primarily housewives dependent on their husband's income, they want to sell food. Limited income and small business capital make it difficult for them to rent a place to sell. High rental costs create an imbalance between income and expenses, ultimately causing their capital to dwindle as they incur losses. The problem that occurs is their inability to create video content to promote their sales. The purpose of this activity is to provide training for the women of Jatiendah Village on how to create video content using the CapCut application. The method used is Asset Based Community Development (ABCD) which develops the ability to make videos. As a result, the women were very enthusiastic about learning the new things. The conclusion of this activity is that Jatiendah villagers benefit from knowledge after being given training in video making and video editing with Capcut. Abstrak— Warga RT 5, RW 3, Desa Jatiendah, sebagian besar berpenghasilan sebagai pekerja bangunan, membuka warung, dan menjual makanan. Untuk ibu-ibu warga desa Jatiendah yang kebanyakan ibu rumah tangga dan bergantung pada penghasilan suaminya, membuat mereka ingin berjualan makanan. Penghasilan yang terbatas dan modal usaha yang kecil membuat mereka kesulitan untuk menyewa tempat berjualan. Sewa tempat yang mahal membuat pemasukan dan pengeluaran menjadi tidak seimbang. Akhirnya modal habis karena mereka merugi. Permasalahan yang terjadi adalah ketidak mampuan mereka untuk membuat konten video untuk mempromosikan jualannya. Tujuan kegiatan di sini adalah memberi pelatihan kepada ibu-ibu warga desa Jatiendah untuk membuat konten video dengan aplikasi Capcut. Metode yang digunakan adalah Asset Based Community Development (ABCD) yang mengembangkan kemampuan membuat video. Hasilnya ibu-ibu sangat antusias belajar hal baru yang mereka dapatkan. Simpulan dari kegiatan ini warga desa Jatiendah mendapat manfaat pengetahuan setelah diberi pelatihan pembuatan video dan editing video dengan Capcut.